2018
DOI: 10.1080/17518369.2018.1438696
|View full text |Cite
|
Sign up to set email alerts
|

Response of Antarctic sea-ice algae to an experimental decrease in pH: a preliminary analysis from chlorophyll fluorescence imaging of melting ice

Abstract: Microorganisms confined to annual sea ice in the Southern Ocean are exposed to highly variable oxygen and carbonate chemistry dynamics because of the seasonal increase in biomass and limited exchange with the underlying water column. For sea-ice algae, physiological stress is likely to be exacerbated when the ice melts; however, variation in carbonate speciation has rarely been monitored during this important state-transition. Using pulse amplitude modulated fluorometry (Imaging-PAM, Walz), we documented in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 53 publications
1
7
0
1
Order By: Relevance
“…The constant for SO 4 − was determined by Dickson (1990) No or very minor negative effects of increased pCO 2 have previously been reported on the growth of N. lecointei at −1.8 °C (Torstensson et al 2013(Torstensson et al , 2015b, which is consistent with this study. By the end of the experiment in the present study, however, we observed a 16% increase in NPQ and a 14% increase in TBARS content at high compared to low pCO 2 , indicating that ocean acidification may lead to higher PAR sensitivity in N. lecointei, similar to that seen in natural sea-ice algal assemblages (Castrisios et al 2018) and in mesophilic diatoms (Gao et al 2012). Radiation stress can be coupled with increased lipid peroxidation in Antarctic microalgae (Buma et al 2006), which may have been coupled with a mismatch in PSII efficiency and reactive oxygen species scavenging as a result of lowered medium pH.…”
Section: Discussionsupporting
confidence: 59%
“…The constant for SO 4 − was determined by Dickson (1990) No or very minor negative effects of increased pCO 2 have previously been reported on the growth of N. lecointei at −1.8 °C (Torstensson et al 2013(Torstensson et al , 2015b, which is consistent with this study. By the end of the experiment in the present study, however, we observed a 16% increase in NPQ and a 14% increase in TBARS content at high compared to low pCO 2 , indicating that ocean acidification may lead to higher PAR sensitivity in N. lecointei, similar to that seen in natural sea-ice algal assemblages (Castrisios et al 2018) and in mesophilic diatoms (Gao et al 2012). Radiation stress can be coupled with increased lipid peroxidation in Antarctic microalgae (Buma et al 2006), which may have been coupled with a mismatch in PSII efficiency and reactive oxygen species scavenging as a result of lowered medium pH.…”
Section: Discussionsupporting
confidence: 59%
“…Chlorophyll a fluorescence was measured using a Maxi imaging pulse amplitude modulated fluorometer (I-PAM, Walz Germany) using the methods described by Castrisios et al (2018). Briefly, extracted ice-cores were cut into 50 × 50 × 30 mm blocks, placed in black plastic containers, and carefully aligned into position on the I-PAM stage.…”
Section: Photophysiology Chlorophyll a And Species Compositionmentioning
confidence: 99%
“…Briefly, extracted ice-cores were cut into 50 × 50 × 30 mm blocks, placed in black plastic containers, and carefully aligned into position on the I-PAM stage. The saturation pulse method was then used to determine the maximum quantum yield by measuring the minimum (Fo) and maximum (Fm) fluorescence of the inverted algae biofilm in a dark-adapted state (Castrisios et al, 2018). Fv/Fm is a sensitive indicator of photosystem potential and a proxy for cellular health in photosynthetic organisms.…”
Section: Photophysiology Chlorophyll a And Species Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…84 No Brasil, Kerr e colaboradores identificaram os recifes coralinos, 85 a plataforma de rodolitos (algas calcárias) ao largo dos litorais do Espírito Santo e Bahia, e as regiões de ressurgência da costa e da plataforma como áreas mais sensíveis à acidificação, apesar dos conhecimentos atuais ainda não permitirem apontar efeitos diretos. A comunidade científica brasileira é atuante neste tema através da Rede Brasileira de Pesquisa em Acidificação dos Oceanos (BrOA) 86 e vem abordando o tema no sentido de melhorar a qualidade dos dados observacionais com protocolos adotados internacionalmente, 85,87 através de experimentos com organismos para entender a resposta à acidificação [88][89][90][91] e estudos de observação na plataforma e áreas oceânicas (e.g. 92,93 ) especialmente no que diz respeito à porção oeste do Oceano Atlântico Equatorial e Sul.…”
Section: Figuraunclassified